PENGEMBANGAN OPEN WEB COORDINATE TRANSFORMATION SERVICE (WCTS) - Ferdiansyah, Harry (GEOMATIKA, 2009)
The use of web service for spatial data is getting more popular nowadays, supported by the Open Geospatian Consortium (OGC) as the standard provider has made the development of exchange and visualisation of internet-based spatial data to be more popular. The utilisation of different spatial reference systems has made the need for web service for transformation to become a certainty. There are many web services offering spatial data transformation, but most of them use manual system to input data to be processed, so that not all of them fulfil the OGC specification to do the complete transformation features. This paper is aimed at offering the alternative solution for the coordinate transformation problem mentioned, through a development of a web service using the Geographic Markup Language (GML). Keywords: web service, coordinate transformation, spatial data processing. ABSTRAKPenggunaan web service untuk data spasial semakin populer saat ini, didukung oleh Open Geospatial Consortium (OGC) sebagai penyedia standar membuat perkembangan akan perukaran dan visualisasi data spasial berbasis internet semakin memasyarakat. Penggunaan sistem referensi spasial yang berbeda-beda menjadikan kebutuhan akan web service untuk transformasi koordinat sebuah keniscayaan. Terdapat banyak website yang menawarkan transformasi data spasial, tetapi sebagian besar masih menggunakan metode manual untuk memasukkan data poin yang akan diproses, sehingga tidak seluruhnya mendukung spesifikasi OGC untuk melakukan transformasi fitur spasial secara lengkap. Tulisan ini bertujuan untuk menawarkan alternatif pemecahan masalah dalam transformasi koordinat tersebut diatas, melalui pengembangan sebuah web service dengan optimasi penggunaan Geographic Markup Language (GML). Kata kunci: web service, transformasi koordinat, pemrosesan data spasial